Inversion Reveals Perceptual Asymmetries in the Configural Processing of Human Body - Marzoli, Daniele (Front Behav Neurosci, 2017)
Ambiguous human bodies performing unimanual/unipedal actions are perceived more frequently as right-handed/footed rather than left-handed/footed, which suggests a perceptual and attentional bias toward the right side of others’ body. A bias toward the right arm of human bodies could be adaptive in social life, most social interactions occurring with right-handed individuals, and the implicit knowledge that the dominant hand of humans is usually placed on their right side might also be included in body configural information. Given that inversion disrupts configural processing for human bodies, we investigated whether inversion reduces the bias toward the right side of human bodies. Consistent with our hypothesis, when presented with ambiguous stimuli depicting humans performing lateralized actions or movements, participants perceived a greater proportion of right-handed figures when the stimuli were shown upright than when the stimuli were shown inverted. The present findings seem to confirm our hypothesis that body configural information may include some form of knowledge about the probable handedness of other individuals, although alternative accounts involving the role of experience cannot be ruled out.